Faktor-Faktor yang Berhubungan dengan Kepatuhan Ibu Hamil dalam Mengkonsumsi Tablet Fe Dipuskesmas Kabanjahe Kecamatan Kabanjahe Kabupaten Karo Provinsi Sumatera Utara Tahun 2024 - Juni Sari Elisabet Purba; Basaria Manurung (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Nutritional intake of pregnant women affects fetal growth. Good nutritional status in pregnant women can prevent low birth weight (LBW) and stunting (short). This study aims to determine the factors associated with the compliance of pregnant women in consuming Fe tablets at the Kabanjahe Health Center, Kabanjahe District, Karo Regency, North Sumatra Province in 2024. This type of research is a study with a cross-sectional design. In cross-sectional research, the cause or risk and effect variables or cases that occur in the research object are measured or collected simultaneously (at the same time). The population is all pregnant women at the Kabanjahe Health Center, Kabanjahe District, Karo Regency, as many as 36 people. The number of samples used was 36 people obtained using the Total sampling technique. The data analysis technique used chi-square analysis. The results obtained in this study were from 36 respondents, there was a relationship between knowledge and compliance of pregnant women in consuming Fe tablets at the Kabanjahe Health Center, Kabanjahe District, Karo Regency, North Sumatra Province in 2024, with a p-value of 0.001 (p-value <0.05), Pregnant Women TM III, there was a relationship between husband and family support for compliance of pregnant women in consuming Fe tablets at the Kabanjahe Health Center, Kabanjahe District, Karo Regency, North Sumatra Province in 2024, with a p-value of 0.000 (p-value <0.05), there was a relationship between ANC visits and compliance of pregnant women in consuming Fe tablets at the Kabanjahe Health Center, Kabanjahe District, Karo Regency, North Sumatra Province in 2024, with a p-value of 0.002 (p-value <0.05), there was a relationship between motivation and compliance of pregnant women in consuming Fe tablets at the Kabanjahe Health Center, Kabanjahe District, Karo Regency, North Sumatra Province North Sumatra in 2024, with a p-value of 0.021 (p-value < 0.05).